E-Service quality : Malaysian perceptions / Noor Habibah Arshad, Norjansalika Janom and Isnainy Mohd Idris - Arshad, Noor Habibah; Janom, Norjansalika; Mohd Idris, Isnainy (Fakulti Teknologi Maklumat dan Sains Kuantitatif, 2005)
The opportunities and challenges offered by the 'electronic retail market place' are certainly generating both excitement and concern within the business community. However, Internet retailing is still very much in its infancy especially in Malaysia. One of the factors to boost the usage of electronic retail market place is the service quality. Service quality is increasingly recognized as an important aspect of electronic retail marketplace. Service quality is the key determinant for successful e-commerce. Gummesson (1979) was one of the first to suggest that the concept of service quality was strongly related to perceptions and trust. This study aims to gather information about consumer perceptions of Internet retail service quality based on selected dimensions, which represent overall quality of Internet retailing. The dimensions are reliability, access, security, efficiency, ease of use and information. Other objectives are to see whether demographic profile and Internet usage would influence the perception on the e-service quality.